The Effect of Breast Size on Spinal Posture - Michalik, Roman; Kuehlmann, Britta; Wild, Michael; Siebers, Hannah Lena; Migliorini, Filippo; Eschweiler, Joerg; Betsch, Marcel (Aesthetic Plastic Surgery, 2022)
Macromastia can cause various clinical symptoms, such as low back and shoulder pain as well as sacro-iliac disorders. Because of these symptoms, some women consider breast reduction surgery. So far there does not exist a clear correlation between breast size and back pain. Purpose of this study was to evaluate if increasing breast size has a measurable effect on women’s posture using radiation free surface topography. A total of 100 women were grouped according to their breast cup size into four groups (Cup Size: A, B, C, D). All female subjects were measured with a surface topography system, and their spinal posture and pelvic position were analysed accordingly. Our results showed that cup size affects kyphotic angle (p = 0.027) and surface rotation (p = 0.039) significantly. Kyphotic angle increased with cup size. Multiple linear regression analysis, however, revealed that the body mass index has the greatest influence on woman’s posture, showing significant correlation to kyphotic and lordotic angle (p < 0.01), as to trunk (p < 0.01) and pelvic inclination (p = 0.02). This is the first study that evaluates the influence of increasing breast size on posture using surface topography. The results match with previous studies using different measuring techniques. However, the great influence of BMI on posture is also confirmed. Therefore, in clinical practice these factors should be taken into account and be approached. Surface topography seems to be a promising tool to further investigate the influence of breast size on posture. Level of Evidence IV This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Back pain; Breast size; Reduction mammaplasty; Spinal posture; Surface topography